Women and the Reformation - Stjerna, Kirsi Irmeli 1963- (Blackwell, 2009)
Women and the Reformation gathers historical materials and personal accounts to provide a comprehensive and accessible look at the status and contributions of women as leaders in the 16th century Protestant world. Explores the new and expanded role as core participants in Christian life that women experienced during the Reformation Examines diverse individual stories from women of the times, ranging from biographical sketches of the ex-nun Katharina von Bora Luther and Queen Jeanne d`Albret, to the prophetess Ursula Jost and the learned Olimpia Fulvia Morata Brings together social history and theology to provide a groundbreaking volume on the theological effects that these women had on Christian life and spirituality Accompanied by a website at www.blackwellpublishing.com/stjerna offering student`s access to the writings by the women featured in the book.